Operational Assistance Policy in Improving The Quality of Early Childhood Education - Wika Karina Damayanti; Sutaryat Trisnamansyah; Dede Khoeriyah; Nandang Koswara (Indonesian Journal Of Educational Research and Review, 2022)
This research is motivated by a large budget for PAUD operations, but in fact the service for early childhood education is relatively low, the gross enrollment rate is low at the PAUD level, and the lack of PAUD education personnel who meet teacher competency standards, there are still many PAUD teachers who come from village cadres. This study aims to analyse implementation of operational assistance policy for the implementation of early childhood education in improving quality of PAUD. This research approach is a qualitative research with case study method. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that in the preparation of the budget for the BOP carried out at the school it involves the entire school community, namely the principal, teachers, and class coordinators representing the children's parents. Evaluation activities in the PAUD BOP program are carried out routinely and scheduled for activities in schools. The obstacle in the preparation of the BOP is the decrease in the number of children so that it has an impact on the decrease in the regular BOP obtained, this affects the decrease in the budget that has been allocated for several elements of learning. The solution to overcome obstacles in the formulation of BOP PAUD policies is to seek other sources of funds to cover the lack of BOP, namely funds from the Foundation, and sort out the sources of funds for various school expenses.